Pengembangan Media Pembelajaran Interaktif “GIANT” Berbasis Articulate Storyline 3 Pada Mata Pelajaran IPAS Bagian Tubuh Tumbuhan Kelas IV Sekolah Dasar - Sofiani, Ratna; Damayani, Aries Tika; Sundari, Riris Setyo (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to develop an interactive IPAS learning media based on Articulate Storyline 3 for the topic of plant parts, intended for fourth-grade elementary school students. The background of the research is the low level of students' understanding of the material due to monotonous teaching methods and the lack of interactive media usage. The study employs a Research and Development (RD) approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The instruments used include validation sheets by material and media experts, as well as practicality questionnaires completed by teachers and students. The validation results showed that the media received an average score of 83.5% (valid), and the material scored 84% (very valid). The practicality test yielded a score of 80% (practical). Therefore, the interactive media "GIANT" is considered suitable for use as an alternative learning tool for IPAS in fourth-grade elementary school.Keywords: Interactive Learning Media, Science (Integrated Science), Articulate Storyline 3, Parts of a Plant.